2019
DOI: 10.1158/1078-0432.ccr-18-3875
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Modifies the Incidence of Graft-versus-Host Disease after Allogeneic Stem Cell Transplantation Depending on the Vitamin D Receptor (VDR) Polymorphisms

Abstract: Purpose: The biologically active metabolite of vitamin D3, 1,25-dihydroxyvitamin D3 (vit D), has immunoregulatory properties via binding vitamin D receptor (VDR). In a prospective trial, we previously reported a reduction in the incidence of chronic GvHD (cGvHD) among patients who received vit D after allogeneic stem cell transplantation (allo-HSCT; Clinical Trials.gov: NCT02600988). Here we analyze the role of patients and donors' VDR SNPs on the immunomodulatory effect of vit D.Patients and Methods: Patients… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…In an HSCT setting, vitamin D deficiency is considered a common complaint that may affect the treatment outcome (62). Genetic polymorphisms of the VDR have been shown to alter the immunomodulatory effect of vitamin D (63). Consistent with these observations, our results suggest a role for VDR in aGvHD-pathogenesis and present 24 VDR-associated biological processes.…”
Section: Discussionsupporting
confidence: 86%
“…In an HSCT setting, vitamin D deficiency is considered a common complaint that may affect the treatment outcome (62). Genetic polymorphisms of the VDR have been shown to alter the immunomodulatory effect of vitamin D (63). Consistent with these observations, our results suggest a role for VDR in aGvHD-pathogenesis and present 24 VDR-associated biological processes.…”
Section: Discussionsupporting
confidence: 86%
“…Further evidence for a causal link is provided by the fact that vitamin D receptor (VDR) gene polymorphisms are associated with development of aGvHD in humans [11]. In line, a recent study reported a decreased incidence of cGvHD upon vitamin D supplementation of patients with a certain VDR genotype [12]. Interestingly, VDR gene polymorphisms have also been characterized as risk factors for graft rejection after liver Tx [36].…”
Section: Discussionmentioning
confidence: 98%
“…A number of reports has described insufficiency for 25-hydroxyvitamin-D3 in patients undergoing allogeneic HSCT [2,5,6,19]. As a consequence, we and others used different approaches to increase vitamin D levels in patients undergoing HSCT [7,12,[20][21][22]. At present, the role of 25-hydroxyvitamin-D3 for survival after HSCT has been examined in eight studies [3-5, 7, 18, 23-25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of VDR gene polymorphisms with major clinical outcomes following HSCT has been investigated in different studies with inconclusive results (116,143,(146)(147)(148)(149)(150). Therefore, further research in this field is warranted with larger study samples, including more recipients of different donor types (unrelated, haploidentical).…”
Section: Vdr As Biomarker In Hsctmentioning
confidence: 99%